Pemanfaatan Komunikasi Interpersonal dalam Pemberian Layanan Administrasi di Puskesmas Ballaparang Kecamatan Rappocini Kota Makassar - Rahmadani, Indah; Lahi, Beddu; Shofiyah, St. (Jurnal Publisitas, 2025)
The importance of effective interpersonal communication between administrative staff and patients in supporting quality services, especially now that the Ballaparang Community Health Center, Rappocini District, Makassar City has provided an online registration administration service channel via WhatsApp. The approach used is a qualitative approach with interview, observation and documentation methods. The focus of this study is the effectiveness of interpersonal communication which includes five main aspects, namely: openness, empathy, positive attitude, supportiveness, and equality. Based on the results of field research on the use of interpersonal communication in providing administrative services at the Ballaparang Community Health Center, Rappocini District, Makassar City, it can be explicitly concluded that the indicators of the effectiveness of interpersonal communication have been running, the five aspects of openness, empathy, positive attitude, supportiveness, and equality have been implemented quite well by administrative staff. When the indicators of the effectiveness of interpersonal communication are applied consistently, this has an impact on increasing efficiency, increasing patient satisfaction, improving the image of the community health center as a professional and humanistic service institution. Keywords: interpersonal communication, effectiveness, administrative services